2011
DOI: 10.1021/bm1011695
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) Microparticles Produced by Precipitation Polymerization in Aqueous Solution

Abstract: Methods were developed to perform precipitation photopolymerization of PEG-diacrylate. Previously, co-monomers have been added to PEG when precipitation polymerization was desired. In the present method, the LCST of the PEG itself was lowered by addition of the kosmotropic salt sodium sulfate to an aqueous solution. Typical of a precipitation polymerization, small microparticles or microspheres (1–5 micron) resulted with relatively low polydispersity. However, aggregate formation was often severe, presumably d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…A sample size of N>1000 microgels was utilized to determine average particle size. The polydispersity of the microgels was calculated as: PDI=Vi2ViViN. where V i is the volume of microsphere i and N is the total number of microgels [21]. The size of the microgels was also measured using dynamic light scattering (DLS; 90Plus Particle Size Analyzer, Brookhaven Instruments) at a scattering angle of 90° and wavelength of 658 nm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A sample size of N>1000 microgels was utilized to determine average particle size. The polydispersity of the microgels was calculated as: PDI=Vi2ViViN. where V i is the volume of microsphere i and N is the total number of microgels [21]. The size of the microgels was also measured using dynamic light scattering (DLS; 90Plus Particle Size Analyzer, Brookhaven Instruments) at a scattering angle of 90° and wavelength of 658 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the improved thermal, chemical, and physical properties exhibited by microgels, these particles are currently being investigated for use in a number of applications, including controlled drug delivery [1417] and tissue engineering applications [1820]. The preparation of microgels formed via precipitation polymerization creates highly crosslinked microgels with relatively low polydispersity [19, 21] in an aqueous environment. Typically phase separation must be performed at high temperatures, however several groups have demonstrated that the inclusion of kosmotrophic salts allows for precipitation at more physiologically relevant temperatures [2123].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Flake et al have also reported precipitation polymerization synthesis of monodisperse PEG microgels between 1 to 5 μm in diameter. 17 …”
Section: Fabrication Methods For Microgelsmentioning
confidence: 99%